Preparation of abdominal computed tomography data set for patients with abdominal aortic aneurysm - Maria R. Kodenko; Tatiana A. Makarova (Digital Diagnostics, 2023)
BACKGROUND: Artificial intelligence (AI) technologies are actively implemented in the processing and analysis of diagnostic medical images. The accuracy and reliability of AI algorithms are determined by the amount and quality of training data sets. Currently, a need exists for increased open access data sets, particularly abdominal aortic CT angiographic studies (CTA). Limitations of existing abdominal aortic CTA data sets are binary labeling (classification of the entire study) and small number of examinations. In addition, most examinations do not contain signs of aortic pathology, which, given its variability, significantly limits their use for AI training, since the target of such algorithms is the detection of pathology.